PENCIPTAAN KARYA WAYANG PREMBON ''PUGPUG KI BALIAN BATUR'' - Satria Darmawibawa, Anak Agung Putu; Kodi, I Ketut; Brata Natyam, I Bagus Wijna (Pusat Penerbitan LP2MPP ISI Bali, 2025)
This article presents the creative research and realization of the shadow puppet performance Wayang Prembon “Pugpug Ki Balian Batur”, an innovative work that transforms the traditional Balinese Prembon dramatari into the medium of wayang. The study is motivated by the lack of scholarly and artistic attempts to adapt Prembon into puppet theatre, despite its historical and cultural significance in Bali. The creative methodology employed was Asta Widhi Kawya, the eightfold principle of artistic creation, encompassing contemplative reflection, narrative construction, vocal and movement training, scenographic design, aesthetic synthesis, and final staging. The process involved documentation, observation of rehearsals, and interviews with key informants, analyzed through descriptive-reflective approaches. The performance was structured by integrating narrative from Babad Ki Balian Batur with elements of wayang babad, wayang arja, Balinese topeng, music, and ritual practice. The resulting work reveals a unique synthesis that balances tradition and innovation, producing a performance that is aesthetically engaging, culturally grounded, and spiritually meaningful. The novelty of this research lies in offering the first model of Wayang Prembon based on historical babad sources, demonstrating how creative practice can simultaneously preserve tradition and generate new performative forms within contemporary Balinese pedalangan.